The role of landscape management in the fight against extreme poverty - Kató, Eszter; Nádasy, László (4D Journal of Landscape Architecture and Garden Art, 2015)
1.2 million people in Hungary live in extreme poverty, most of them in the 36 districts marked for development by complex programmes. As social conditions have an impact on landscape as well, landscape management needs to address this sad but widespread issue. However, good practices in this field, which – with years or even decades of work – have achieved permanent positive changes, show that there is indeed hope, which a fully established landscape management system might help realize.